Effects of ammonia loading on lysine utilization by growing cattle - Hussein, Ali Hussein (Kansas State University, 2015)
Six ruminally-cannulated Holstein steers (202 ± 15 kg) were used to study the effects of ruminal ammonia loading on whole-body lysine utilization. Steers were housed in metabolism crates and used in a 6 × 6 Latin square design. All steers received 2.52 kg of DM/d of a diet (10.1% CP) containing 82% soybean hulls, 8% wheat straw, 5% cane molasses, and 5% vitamins and minerals. Ten g/d of urea was infused continuously into the rumen of all steers to ensure adequate ruminal ammonia concentrations; concurrently, steers were ruminally infused continuously with 200 g/d acetic acid, 200 g/d propionic acid, and 50 g/d of butyric acid and abomasally infused with 300 g/d of glucose continuously to increase energy supply without increasing microbial protein supply. Steers were also abomasally infused continuously with an excess of all essential amino acids except lysine to ensure that lysine was the only limiting amino acid. Treatments were arranged as a 3 × 2 factorial with 3 additional levels of urea (0, 40, or 80 g/d) continuously infused ruminally to induce ammonia loading and 2 levels of lysine (0 or 6 g/d) continuously infused abomasally. Treatments did not affect fecal N output (P = 0.37). Lysine supplementation decreased (P < 0.01) urinary N excretion from 51.9 g/d to 44.3 g/d, increased (P < 0.01) retained N from 24.4 to 33.3 g/d, and tended (P = 0.09) to reduce plasma urea-N. Urea infusions linearly increased retained N (26.7, 28.8, and 31.1 g/d; P = 0.05) and also linearly increased (P < 0.01) urinary N excretion (31.8, 48.1, and 64.4 g/d), urinary urea (21.9, 37.7, and 54.3 g/d), urinary ammonia (1.1, 1.4, and 1.9 g/d), and plasma urea (2.7, 4.0, and 5.1 mM) for 0, 40, and 80 g urea/d, respectively. Assuming that retained protein is 6.25 × retained N and contains 6.4% lysine, the incremental efficiencies of infused lysine utilization were 51, 59, and 69% for steers receiving 0, 40, and 80 g/d of urea, respectively, suggesting that the ruminal ammonia loads might improve the efficiency of lysine utilization; this is supported by the observed increases in whole-body protein deposition in response to ammonia loading of our steers that were, by design, lysine deficient.
Keywords: Amino acids; Ammonia; Cattle; Lysine; Nitrogen retention; Animal Sciences (0475)